Large electrocaloric effects induced by multidomain-to-monodomain transition in ferroelectrics with electrical inclusions - Huang, Cheng; Wang, Xiaojun; Zhao, Jinbo (Frontiers in Energy Research, 2023)
The electrocaloric effect (ECE) depends on the sudden change of the polarization field during ferroelectric phase transition near the Curie temperature. Similarly, giant ECE can be found enormously during the domain structure transition from multidomain to monodomain process in ferroelectrics. To reveal the mechanism with the effects of the electric inclusions, the ECE of PbTiO3 (PTO) ferroelectric solids under electric loads is investigated by phase-field simulation. The giant ECEs of ferroelectric materials containing three kinds of electric inclusions, namely, air, silicone oil, and water, are discussed in detail under applied electric fields. The results suggest that an unusual ultrahigh negative ECE (−9.30 K) and a large EC strength (∆T/∆E=0.237 KmMV−1 are achieved near room temperature (about 50°C) in ferroelectrics containing water inclusion. The results indicate that electric inclusions generate high electrostatic energy under electric loads to break through the energy barrier and play an importation role in the ECE. In summary, the works may provide a better way to obtain the giant ECE and large EC strength close to room temperature by effectively regulating the dielectric constant of the electric inclusion and the increment of the applied electric field.